Kajian analisis dari Risalah Nur oleh Imam Badiuzzaman Said Nursi untuk pembentukan minda yang sejahtera = An analytical inquiry into "Risalah nur" by Imam Badiuzzaman Said Nursi: a scholarly examination of its relevance in cultivating peaceful cognitive state - Fatah Yasin, Raudlotul Firdaus; Fatah Yasin, Mohammad Dhiya’ul Hafidh; Fatah Yasin, Muhammad Muthi’ul Haqq (Kolej Universiti Islam Perlis (KUIPs), 2023)
Said Nursi was a figure who brought about a wave of change in the post-Islamic Caliphate era, hence being hailed as Badiuzzaman. In the face of the secular Turkish authorities’ actions of eradicating the Muslim identity, he became the center and beacon for the Turkish Muslim community in search of light. However, his influence was not limited to Turkey alone but also served as a reference for the global Islamic community, even until today. His works, especially the Risale-i Nur (Epistles of Light), have had a profound impact on individuals experiencing mental confusion, emotional distress, and in need to liberate themselves from paying attention only on this narrow world to the vast realms of both this life and the hereafter. This provides a solution by presenting the concept of a peaceful and independent mind in the form of analogies and rational scientific discussions, which is suitable for application in the context of mental well-being, a matter that is increasingly critical in today’s world. This study aims to analyze the concept of constructing a sound and independent mind from the Risale-i Nur by Badiuzzaman Said Nursi. The study utilizes an inductive method to identify the most important content of the relevant work related to the journey of developing a peaceful and independent mind. The study concludes that Nursi’s perspective on the concept of such mindset is holistic, grounded in the texts of the Quran and the Sunnah, especially when considering his framework of its formation starting from the realm of the spirit and the womb, and subsequently linking it to human scientific knowledge. This study contributes to the construction of a concept of sound mind in accordance with Islamic law (Shariah) which is necessary in the context of the current mental health crisis.